2002
DOI: 10.1182/blood-2002-03-0812
|View full text |Cite
|
Sign up to set email alerts
|

P2X1-mediated activation of extracellular signal-regulated kinase 2 contributes to platelet secretion and aggregation induced by collagen

Abstract: Adenosine triphosphate (ATP) and its stable analog, ␣,␤-methylene ATP, activate the platelet P2X 1 ion channel, causing a rapid Ca ؉؉ influx. Here, we show that, in washed apyrase-treated platelets, ␣,␤-methylene ATP elicits reversible extracellular signal-regulated kinase 2 (ERK2) phosphorylation through a Ca ؉؉ -and protein kinase C-dependent pathway. In contrast, high-performance liquid chromatography-purified adenosine diphosphate (ADP) did not trigger ERK2 phosphorylation. ␣,␤-Methylene ATP also activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 31 publications
8
105
1
3
Order By: Relevance
“…These data support the mediating role of secreted ADP and its P2Y 12 receptor in these thrombin effects. Consistent with this conclusion, as well as with previously published data, 15 a selective P2X 1 receptor agonist (␣, ␤-MeATP, 2.5 M) failed to cause any p38 phosphorylation (data not shown). Preincubation of platelets with indomethacin also inhibited thrombin-stimulated p38 activation, Hsp27 phosphorylation, and Pselectin expression to a similar extent as that observed with AR-C69931MX ( Figure 1A).…”
Section: Resultssupporting
confidence: 82%
“…These data support the mediating role of secreted ADP and its P2Y 12 receptor in these thrombin effects. Consistent with this conclusion, as well as with previously published data, 15 a selective P2X 1 receptor agonist (␣, ␤-MeATP, 2.5 M) failed to cause any p38 phosphorylation (data not shown). Preincubation of platelets with indomethacin also inhibited thrombin-stimulated p38 activation, Hsp27 phosphorylation, and Pselectin expression to a similar extent as that observed with AR-C69931MX ( Figure 1A).…”
Section: Resultssupporting
confidence: 82%
“…Vial et al [109] have suggested that in vivo, these ATP-induced reactions could synergize with the platelet response to ADP through the P2Y 1 receptor and amplify the increase in intracellular calcium. Oury et al [110,111] obtained evidence for the importance in hemostasis of a synergy between ADP and ATP released from platelets stimulated by adherence to collagen. They used transgenic mice overexpressing the P2X 1 receptor in the megakaryocyte cell lineage and found that their platelets showed enhanced aggregation and secretion in response to collagen, compared with platelets from wild-type mice.…”
Section: The P2x 1 Receptormentioning
confidence: 99%
“…The ␣,␤-meATP was purified by high pressure liquid chromatography on a Adsorbosphere HS C18, 7-m, 250 ϫ 4.6-mm column (Alltech, Bad Segeberg, Germany) (15,16). Purified samples, lyophilized and adjusted to pH 7.0 with potassium phosphate buffer, were kept at Ϫ80°C and were stable over the time interval studied.…”
Section: Methodsmentioning
confidence: 99%
“…P2X 1 is highly expressed in human platelets and megakaryocytes (13,14); because of the role of Ca 2ϩ /CaM in platelet MLC kinase activation, we have presently investigated the P2X 1 -mediated Ca 2ϩ influx in relation to MLC phosphorylation and platelet shape change. We have previously shown that the P2X 1 -mediated Ca 2ϩ influx triggers phosphorylation of the extracellular signal-regulated kinase (ERK2), a reaction found to contribute to platelet activation and secretion induced by low concentrations of collagen (15,16). We therefore have also investigated the relation between MLC kinase and ERK2 activation during collagen-induced platelet activation, in relation to P2X 1 -mediated Ca 2ϩ influx.…”
mentioning
confidence: 99%